2022
DOI: 10.3390/su15010635
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of Food-Waste-Reduction Measures by Converting Surplus Food into Processed Food Products for Human Consumption

Abstract: Food waste is a major challenge for society as it causes economic, environmental and social problems. Many food-waste-reduction measures aim to prevent food waste at the source or by redistributing surplus food via donation. However, it would also be useful to evaluate surplus-food redistribution, where surplus food can be made available for human consumption by valorization (recycling). This paper evaluates food-waste-reduction measures, where surplus food is converted into processed food products for human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In total, two companies took up the offer to have their actions evaluated. The evaluation of these actions is beyond the scope of this paper and can be found in Lehn and Schmidt [41] and Lehn et al [42]. The first action refers to the conversion of surplus food into high-quality end products.…”
Section: Sustainability Assessment Of Specific Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, two companies took up the offer to have their actions evaluated. The evaluation of these actions is beyond the scope of this paper and can be found in Lehn and Schmidt [41] and Lehn et al [42]. The first action refers to the conversion of surplus food into high-quality end products.…”
Section: Sustainability Assessment Of Specific Actionsmentioning
confidence: 99%
“…In cooperation with various start-ups, retail company PENNY promoted products made from food with minor defects or from overproduction that were previously not intended for human consumption with a display in one of their stores to increase awareness of the issue of FW within the value chain. In the project period of five months, 19 kg of food was saved from being wasted, and it could be shown that most of the new products created had a positive greenhouse footprint [41]. The second action was a trail of a time-temperature indicator on salmon by HelloFresh.…”
Section: Sustainability Assessment Of Specific Actionsmentioning
confidence: 99%
“…Therefore, the product storage strategy speaks volumes about the company's commitment to social responsibility. It describes the company's measures to reduce energy consumption and maximise storage capacity, and eliminates the need for plastic bags and display shelving in their product packaging [4,29,48,55,56].…”
Section: Literature Review For Gap Identificationmentioning
confidence: 99%
“…Environmental care was the driving force rather than financial gain or economic efficiency as it ensures that businesses survive in the longer run [1]. Several critics and academics have discussed the concerns around sustainable business operations, such as developing a generalised retail charter that could steer towards the support for all stakeholders, exploring food waste at retail stores, shift of thinking for economic connection of sustainability and CSR, transformations needed, sustainable retail store brand experience, business model innovations, retail centred sustainability issues of infrastructure, energy usage, and overall end-to-end operations [4][5][6]. There has been continuous struggle for examining the incorporation of environmental considerations into commercial objectives, turning them green.…”
Section: Introductionmentioning
confidence: 99%